Konstruksi Sosial Otoritas Kiai dan Kekerasan Seksual di Pondok Pesantren: Studi Kasus Putusan Pengadilan Nomor 136/Pid.Sus/PN Smp - Ulinnuha Abdurrahman; Khanabi Alwi; Ahmad Wildan Rofrofil Akmal; Alief Abdul Haris (Muhammadiyah University of Surabaya, 2026)
This study aims to analyze the social construction of kiai authority within the pesantren tradition that enables the abuse of power in the form of sexual violence against female students, as well as to examine how state law delegitimizes such authority through the Sumenep District Court Decision Number 136/Pid.Sus/PN Smp. This research employs a normative legal research method using statutory approach and case approach. The research data consist of primary and secondary legal materials analyzed descriptively and analytically through Peter L. Berger’s social construction theory. The findings reveal that kiai authority is formed through the processes of externalization, objectification, and internalization, positioning the kiai as a religious figure possessing strong moral and spiritual legitimacy. This condition creates hierarchical power relations that encourage the absolute obedience of students, thereby opening opportunities for the manipulation of authority, intimidation, and sexual violence. The court decision in this case demonstrates that state law functions as a corrective mechanism that dismantles the social construction of kiai authority when it is used to legitimize criminal acts. The novelty of this study lies in positioning a court decision as a social archive to explain the delegitimization of kiai authority through Peter L. Berger’s social construction theory, thereby extending socio-legal analysis within the pesantren context. The findings imply the need to strengthen institutional accountability mechanisms and student protection systems to ensure that religious legitimacy cannot be misused to justify criminal conduct. This study emphasizes the importance of strengthening student protection mechanisms, institutional supervision within pesantren, and legal awareness to prevent the abuse of religious authority. Keywords: Kiai, Pesantren, Sexual Violence, Social Reconstruction